TAFSIR VIRUS (FAUQA BA'ÅªDHAH): KORELASI COVID-19 DENGAN AYAT-AYAT ALLAH - Wathoni, Lalu Muhammad nurul; nursyamsu, nursyamsu (UIN Mataram, 2020)
In the Qur'an, Allah entrusts many messages through parables about animals. One of the unique animals that Allah uses as tamtsÄ«l (permisalan) in the Koran is a virus (fauqa baÅ«dhah) the smallest animal from a mosquito (baÅ«dhah), which is written in Surah al-Baqarah verse 26. If examined in the context of parables The facts of the verses of Allah will be found. Nature and everything there are verses kauniyah as a knife of analysis that is able to peel the signs of God's power contained in the revelation of God as a qouliyah verse. Then the verse is intriguing to be studied in terms of the present and present contexts, paying attention to the end of 2019, the world was shocked by the spread of the corona virus, known as covid-19. So named because of its emergence at the end of 2019 which is still spreading in the middle of 2020 with no knowing when it will end, until now it has claimed the lives of millions of people. In this study the authors used a descriptive analysis method, by examining the interpretations of some classical to contemporary commentators, such as Athari, Atharihar, Al-Maraghi, Imam Nawawi, Hamka, and Quraish Shihab. This is intended to find out the interpretation of some commentators, then reveal the content of science in Surah al-Baqarah verse 26, and bring up the message or wisdom contained therein. The results of this study indicate; First, according to modern commentators, fauqa baudd is interpreted as a germ and a virus. Second, modern science has proven that something that is considered trivial like a virus, can actually deliver signs of God's power that is so great. Third, man, it is classified into two in addressing Covid-19, which is the attitude of underestimating the corona virus so that it does not make a lesson on the pandemic disaster and the attitude of the muhasabah themselves to return to God and follow the direction of religious and government figures in addressing Covid-19.